2020
DOI: 10.1371/journal.pone.0236587
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of kinesiology tape tension on soleus muscle h-reflex modulations during lying and standing postures

Abstract: Kinesiology tape (KT) has been widely used in the areas of sports and rehabilitation. However, there is no gold standard for the tape tension used during a KT application. The purpose of this study was to examine the effects of KT application with different tension intensities on soleus muscle Hoffmann-reflex (H-reflex) modulation during lying and standing postures. Fifteen healthy university students were tested with 3 tape tension intensities during separate visits with a randomized sequence: tape-on no tens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Different KT tensions were not found to have positive effects among healthy individuals for quadriceps strength, 84,85 knee joint range of motion, 85 lower extremity hop test, 84 the gastrocnemius and soleus H-Reflex, 86,87 and EMG activity of the quadriceps and hamstrings during a loaded squat exercise. 88 However, other researchers have reported that KT does facilitate the H-Reflex 89 and shoulder muscle EMG activity 90 among healthy individuals.…”
Section: Clinical Application Of Ktmentioning
confidence: 87%
“…Different KT tensions were not found to have positive effects among healthy individuals for quadriceps strength, 84,85 knee joint range of motion, 85 lower extremity hop test, 84 the gastrocnemius and soleus H-Reflex, 86,87 and EMG activity of the quadriceps and hamstrings during a loaded squat exercise. 88 However, other researchers have reported that KT does facilitate the H-Reflex 89 and shoulder muscle EMG activity 90 among healthy individuals.…”
Section: Clinical Application Of Ktmentioning
confidence: 87%
“…The tension of elastic tape is exponentially correlated to force generation 22 . However, the effects of different tension degrees of taping to neuromuscular stimulation are still equivocal.…”
Section: Introductionmentioning
confidence: 99%
“…Shakeri et al 23 found elastic tape increased muscle strength, but the different tension was not related to increased muscle strength. Chen et al 22 showed the different tension had no effect on modulating sensorimotor activity. Craighead et al 24 showed the microvascular skin blood flow increased after applied Kinesio tape, but it was not related to degree of tape tension.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent work conducted by Chen et. al on the triceps surae muscle during both lying and standing postures indicates that the change in intensity of tension of the KT does not have much effect on the spinal motor neuron excitability; therefore, in terms of modifying sensory-motor activity, the tension applied during a KT application should not be an issue [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%